Variasi Musiman Suhu Dan Klorofil-a Serta Hubungan dengan Hasil Tangkapan Ikan Kembung (Rastrelliger sp.) Laut Natuna - Hanafi Hanafi; Apriansyah Aprinsyah; Ikha Safitri (Jurnal Kelautan Tropis, 2025)
The Natuna Sea, renowned for its abundant fishery resources, serves as a primary destination for both local and international fishermen. This study focuses on examining the seasonal variations in sea surface temperature (SST) and chlorophyll-a concentrations, as well as their correlations with the catch rates of mackerel (Rastrelliger sp.). Employing climatological analysis, Catch Per Unit Effort (CPUE), and correlation techniques, this research utilizes satellite imagery data from the Marine Copernicus program for chlorophyll-a and SST, alongside catch data obtained from the Pemangkat Fish Landing Port using purse seine and gillnet methods. The findings indicate significant fluctuations in chlorophyll-a and SST that influence the productivity of mackerel catch, with chlorophyll-a levels ranging from 0.40 to 0.69 mg/m³ and an average of 0.37 mg/m³, while SST varies from 27 to 30 °C, averaging 29.11 °C. The peak catch period occurs during the transition seasons I (May) and II (July), providing valuable insights for optimizing capture strategies and serving as a guide for further research on the environmental impacts affecting catch rates.